2018
DOI: 10.1136/sextrans-2018-053830
|View full text |Cite
|
Sign up to set email alerts
|

Increasing proportion of herpes simplex virus type 1 among women and men diagnosed with first-episode anogenital herpes: a retrospective observational study over 14 years in Melbourne, Australia

Abstract: ObjectivesReports of rising herpes simplex virus type 1 (HSV-1) genital infections relative to HSV-2 have been published up to 2006 in Australia. These changes have been attributed to declining childhood immunity to HSV-1. We described the temporal trends of HSV-1 and HSV-2 up to 2017 in Melbourne, Australia, to determine if the earlier trend is continuing.MethodsWe conducted a retrospective review of the medical records of 4517 patients who were diagnosed with first episode of anogenital HSV infection at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Primary infections of HSV-1 are usually established in the oral mucosa, and less frequently in the genital mucosa or other epithelial surfaces at the periphery. While HSV-2 is the main causative agent of genital herpes overall, the main cause of initial genital herpes is HSV-1 in populations such as young women [ 7 , 8 , 9 , 10 ]. Following infection and replication in stratified squamous epithelial cells, the virus infects innervating sensory nerves in the epidermis and undergoes retrograde axonal transport to the cell body.…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Primary infections of HSV-1 are usually established in the oral mucosa, and less frequently in the genital mucosa or other epithelial surfaces at the periphery. While HSV-2 is the main causative agent of genital herpes overall, the main cause of initial genital herpes is HSV-1 in populations such as young women [ 7 , 8 , 9 , 10 ]. Following infection and replication in stratified squamous epithelial cells, the virus infects innervating sensory nerves in the epidermis and undergoes retrograde axonal transport to the cell body.…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…We estimated that in 2016, 491 million people aged 15–49 years had HSV-2 infection, which is almost all sexually transmitted 2. HSV-1, although predominately an oral infection, is increasing as a cause of genital herpes in some settings 3–5. We estimated that 192 million people had genital HSV-1 infection in 2016 2.…”
Section: Introductionmentioning
confidence: 99%
“…In a nationwide study in 1999-2000, which showed 76% of the population carrying HSV1 that differed based on age, race, gender [103] Another study indicated the increasing seroprevalence of HSV-1 as in a study combining 25,372 subjects during 1980 and 2003, 15.8% of tested patients were found positive for HSV-1 in 1980, however, 34.9% were positive in 2003 [104]. Meanwhile in a recent, HSV-1 infection prevalence seems to be higher in female population as a 16% increasal has occured in 2017 compared to the 45% female HSV-1 patients observed in the 2004 data obtained from Melbourne Sexual Health Center, Australia [105].…”
Section: Australiamentioning
confidence: 99%